FORMULASI STRATEGI KEUNGGULAN KOMPETITIF UMKM B2B2C BERBASIS E-COMMERCE - Kilay, Trisye Natalia; Mawar, Sholeha Johat; Wally, Firna (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
Rouze Fashion is a start-up MSME with a hybrid B2B2C business model that combines e-commerce-based procurement and local social networks in areas far from shopping centers, thus requiring the right strategy to maintain competitiveness and business sustainability. This study aims to analyze the right strategy formulation to keep Rouze Fashion growing sustainably. The research uses a descriptive qualitative approach with primary data derived from interviews and questionnaires with business owners. Data analysis techniques use Strength, Weakness, Opportunity & Threat (SWOT) analysis to identify internal and external factors, as well as Quantitative Strategic Planning Matrix (QSPM) to determine the main strategies. The results show that there are three priority strategies that Rouze Fashion must implement, namely maintaining sales based on local trends and culture, optimizing procurement through controlled e-commerce suppliers, and implementing performance-based incentives for third parties. These three strategies are able to address challenges related to supply variability, distribution coordination, and cash flow stability. Practically, these findings can be used as a guide for similar MSMEs, while theoretically, this research enriches the study of Resource Based View (RBV), Transaction Cost Economics (TCE), and Agency Theory in the context of hybrid supply chains.